First-Time Voter Education Through the Democracy Volunteer Movement - Suryanef, Suryanef; Rafni, Al (Journal of Moral and Civic Education, 2020)
Ahead of the 2014 election, the General Election Commission established a group of facilitators to educate the public about the election (voter education), called Democracy Volunteer (Relawan Demokrasi), in cities/regencies throughout Indonesia. Democracy Volunteer is a program aimed at increasing political participation and election quality. One of the target groups for the voter education is first-time voters. First-time voters are perceived to have distinctive political behavior; their political actions are qualitatively different from other segments of voters. They are also classified as the technology savvy generation. This paper intends to elaborate the Democracy Volunteers' efforts in implementing voter education for first-time voters, and reveal the most suitable voter education model for this segment of voters. The research used qualitative method through focus group discussions and in-depth interviews. The results show that a voter education model for first-time voters is needed in order that Democracy Volunteers carry out the voter education effectively in achieving the expected goals.